2014
DOI: 10.1002/tox.22050
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity and DNA damage to zebrafish induced by perfluorooctane sulfonate in the presence of ZnO nanoparticles

Abstract: Perfluorooctane sulfonate (PFOS) and ZnO nanoparticles (ZnO-NPs) are frequently detected in the environment, but few studies have assessed their joint toxicity. In this study, the acute toxicity and chronic toxicity to zebrafish (Danio rerio) induced by PFOS in the presence of ZnO-NPs were investigated, including developmental toxicity and DNA damage. The embryos were exposed to PFOS (only) (0.4, 0.8, and 1.6 mg/L) and PFOS plus ZnO-NPs (0.4 + 50, 0.8 + 50, and 1.6 + 50 mg/L) solutions to evaluate mortality (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 48 publications
3
18
1
2
Order By: Relevance
“…d Average body length, e size of the yolk, and f eye size following treatment, as captured using the HCImage software and analyzed with version 1.52a of the ImageJ software version. c One-way analysis of variance (ANOVA) followed by the Dunnett test was used to compare the groups, **p < 0.01 and ***p < 0.001, n = 20 agreement with previous reports [74,75] (Fig. 4b, c), ZnO showed a significant decrease in the heart rate of the zebrafish embryos as shown in Fig.…”
Section: Exposure To Aeo-7 Induces Cardiac Dysfunction In Zebrafish Esupporting
confidence: 85%
“…d Average body length, e size of the yolk, and f eye size following treatment, as captured using the HCImage software and analyzed with version 1.52a of the ImageJ software version. c One-way analysis of variance (ANOVA) followed by the Dunnett test was used to compare the groups, **p < 0.01 and ***p < 0.001, n = 20 agreement with previous reports [74,75] (Fig. 4b, c), ZnO showed a significant decrease in the heart rate of the zebrafish embryos as shown in Fig.…”
Section: Exposure To Aeo-7 Induces Cardiac Dysfunction In Zebrafish Esupporting
confidence: 85%
“…In disagreement with previous reports [63,64] (Fig. 4B-C), ZnO did not decrease heart rate signi cantly in our animals ( Fig.…”
Section: Exposure To Aeo-7 Induces Cardiac Dysfunction In Zebra Sh Emcontrasting
confidence: 99%
“…Zebra sh have been shown to be a good model for predicting hepatotoxicity [68][69][70], probably because the enzymes and pathways involved in xenobiotic metabolism (e.g., the aryl hydrocarbon receptor and isozymes of cytochrome P-450 and aldehyde dehydrogenase) are all evolutionarily conserved and all functional from the early stages of the development of zebra sh embryos, including our experimental window [63,71,72].…”
Section: At Its Noec Aeo-7 Exerts No Adverse Effect On Hepatic Functmentioning
confidence: 99%
“…Many in vivo studies have shown that ZnO NPs exposure can reduce the heart rate of zebrafish and freshwater fish Catostomus commersonii. 15,44 The heart rate was also reduced in mice after injection of five nanomaterials including ZnO NPs. 45 Our results showed that the electrophysiological properties of hiPSC-CMs were affected by ZnO NPs at insignificantly cytotoxic doses, suggesting that electrophysiological function is a sensitive parameter for indicating the cardiac adverse effect of nanomaterials.…”
Section: Discussionmentioning
confidence: 99%